2021
DOI: 10.3354/ame01970
|View full text |Cite
|
Sign up to set email alerts
|

Temporal variation in community structure of zoosporic fungi in Lake Biwa, Japan

Abstract: Zoosporic fungi play an important role in aquatic environments, but their diversity, especially that of parasitic fungi of phytoplankton, has still not been fully revealed. We conducted monthly analyses of the community structure of zoosporic fungi at a pelagic site in Lake Biwa, Japan, from May to December 2016. Metabarcoding analysis, targeted to a large subunit region of ribosomal DNA in the nano-size fraction of particles (2-20 µm), was carried out on the samples. We also counted large phytoplankton and ch… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
3

Relationship

1
2

Authors

Journals

citations
Cited by 3 publications
(2 citation statements)
references
References 45 publications
0
2
0
Order By: Relevance
“…Chytrid epidemics have been mostly reported from large (e.g. inedible) bloom forming diatom species [ 12 , 71 , 72 ], but we observed that also small-sized diatoms (e.g. Cyclotella spp.)…”
Section: Discussionmentioning
confidence: 58%
“…Chytrid epidemics have been mostly reported from large (e.g. inedible) bloom forming diatom species [ 12 , 71 , 72 ], but we observed that also small-sized diatoms (e.g. Cyclotella spp.)…”
Section: Discussionmentioning
confidence: 58%
“…Interactions between phytoplankton and fungal parasites such as chytrids are key processes in aquatic food webs and ecosystems, potentially driving phytoplankton population and community dynamics (Miki et al 2011, Frenken et al 2017, Song et al 2021 ) and the flow of energy from phyto-plankton to zooplankton via zooplankton grazing on chytrid zoospores, the so-called 'mycoloop' (Kagami et al 2007(Kagami et al , 2011(Kagami et al , 2014. Past studies have estimated the prevalence of infection in natural ecosystems (Ibelings et al 2011, Kagami et al 2012, experimentally quantified the interaction strength (Kagami et al 2004, Frenken et al 2020, and developed mathematical models (Bruning 1991a, Miki et al 2011, Gerla et al 2013, Almocera et al 2018, Frenken et al 2020.…”
Section: Introductionmentioning
confidence: 99%